Operating Costs of Aging Air Force Aircraft: Adjusting for Aggregate Budget Effects. Issue 4 (7th June 2019) - Trunkey, R. Derek
ABSTRACT: The rate at which operating costs grow as aircraft age is important for setting operating budgets and for deciding when to replace aging systems. While studies using data from the 1990's typically found 1–3 percent real rates of growth in operating costs as aircraft age, studies using data from the 2000's found greater rates, for example in the 4–6 percent range. Growth in the total U.S. Air Force budget during the 2000s appears to explain much of the higher estimated annual growth rates in operating costs per flying hour beyond the growth rate intrinsic to the aging of the fleet.